2015
DOI: 10.1136/bmjopen-2014-006963
|View full text |Cite
|
Sign up to set email alerts
|

The stability of weight status through the early to middle childhood years in Australia: a longitudinal study

Abstract: ObjectivesTo investigate the sociodemographic and behavioural factors associated with incidence, persistence or remission of obesity in a longitudinal sample of Australian children aged 4–10 years.SettingNationally representative Longitudinal Study of Australian Children (LSAC).ParticipantsThe sample for this analysis included all children in the Kinder cohort (aged 4–5 years at wave 1) who participated in all four waves of LSAC (wave 1, 2004, aged 4–5 years; wave 2, 2006, aged 6–7 years; wave 3, 2008, aged 8–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 29 publications
5
53
3
Order By: Relevance
“…Eighty‐six citations were excluded (Appendix 3). Thirty‐eight citations met the inclusion criteria for this systematic review, of which 34 were cohort studies , One was an RCT , and 3 were controlled clinical trials where data from the various groups were the study authors combined groups for analysis as a cohort study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty‐six citations were excluded (Appendix 3). Thirty‐eight citations met the inclusion criteria for this systematic review, of which 34 were cohort studies , One was an RCT , and 3 were controlled clinical trials where data from the various groups were the study authors combined groups for analysis as a cohort study .…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies included in this systematic reviewed performed analyses of different exposures and/or outcomes of interest using the same data set, such as Bigornia et al , and Dong et al , Zheng et al , and Zheng et al , Shefferly et al , and DeBoer et al , Millar et al , and Wheaton et al . Study characteristics for each included study were abstracted (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcutaneous fat in 6–9 year old children has been shown to increase even three to fivefold (Nagel et al 2009), which means, even if levels have plateaued, children’s weight status stopped at a very high level. An extensive body of research indicates that overweight and obese children have a higher risk of becoming obese adults than their normal counterparts (Singh et al 2008; Venn et al 2007; Pei et al 2013; Wheaton et al 2015) and a major contributing factor is low levels of physical activity (Hills et al 2011). On the other hand, benefits of a physically active lifestyle for childhood health are well documented (Andersen et al 2006; Janssen and LeBlanc 2010); therefore, the WHO (WHO 2010) developed recommendations for appropriate amounts of physical activity for children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a national survey found that 98% of Australian children aged five to 14 years did not eat the recommended daily serves of fruit and vegetables (Australian Institute of Health and Welfare, 2016), whilst other research discovered two thirds of children exceed recommended sugar intakes, and four fifths exceed recommended saturated fat intakes (CSIRO, 2008). This presents a significant public health challenge as many aspects of eating behaviors, as well as weight status, are formed in childhood and are subsequently difficult to change (Savage, Fisher, & Birch, 2007;Scaglioni, Salvioni, & Galimberti, 2008;Wheaton, Millar, Allender, & Nichols, 2015). This puts individuals at greater risk for developing non-communicable diseases such as diabetes, cardiovascular disease and some forms of cancer in later life (Ebbeling, Pawlak, & Ludwig, 2002), which are presently the biggest causes of disease and disability in many developed countries including Australia (Australian Institute of Health and Welfare, 2016).…”
Section: Introductionmentioning
confidence: 99%